Political and Economic Aspects of Serbo-Russian Relations from the Perspective of Serbian Citizens - Dragan Trailović; Stevan Rapaic (Евразийская интеграция: экономика, право, политика, 2021)
We are witnessing that with the appearance of new global players on the international scene a multipolar world is gradually emerging and a new balance of power is being formed. Given this circumstance, it is very important that all other states clearly define their position towards these emerging poles of power. As Russia appears as one of those poles, it is necessary to look at the position of Serbia concerning political and economic cooperation between the two countries. One of the ways to do that is to look at these issues from the perspective of Serbian citizens. Accordingly, this paper aims to present the basic findings concerning the assessment and opinion of the citizens of Serbia towards political, economic and military cooperation between the Republic of Serbia and the Russian Federation based on the analysis of surveys conducted by the Institute for Political Studies in 2015–2020 period. The authors will also present the basic economic, trade and financial indicators of cooperation between Russia and Serbia, mainly trade relations and foreign direct investment.